The mitogen-activated protein kinase pathway in melanoma part I – Activation and primary resistance mechanisms to BRAF inhibition. (March 2017) - Amaral, Teresa; Sinnberg, Tobias; Meier, Friedegund; Krepler, Clemens; Levesque, Mitchell; Niessner, Heike; Garbe, Claus
Abstract: Mitogen-activated protein kinase (MAPK) pathway has an important role in normal cells and can be activated under physiological conditions. MAPK pathway activation is a fundamental step in several intracellular processes requiring a sequential phosphorylation of the different pathway components. In normal cells, when MAPK pathway activation occurs, it leads to cell growth and differentiation. In order to prevent persistent MAPK pathway activation, physiological upstream negative feedback also takes place. In cells harbouring BRAFV600 mutations, the process leading to MAPK pathway activation is different, and the negative physiological feedback does not exist thus leading to permanent MAPK pathway activation, which ultimately can lead to uncontrolled proliferation. Targeted therapy with rapidly accelerated fibrosarcoma – B (BRAF) and/or mitogen-activated extracellular signal-regulated kinase kinase (MEK) inhibitors is indicated in patients with metastatic melanoma harboring BRAFV600 mutations. However, several different resistance mechanisms to this therapy were identified. In this review, we focus on primary or intrinsic resistance mechanisms to BRAF and MEK inhibition. In this setting, although a BRAF mutation is identified, there is no response to treatment with either BRAF or MEK inhibitor. Highlights: MAPK pathway has an important role in different physiological processes. MAPK pathway re-activation can lead to BRAF inhibition (BRAFi) therapy resistance. No response to BRAFi therapy is associated with primary resistance mechanisms.